A new Martian meteorite from Oman: mineralogy, petrology, and shock metamorphism of olivine-phyric basaltic shergottite Sayh al Uhaymir 150 - Walton, Erin L.; Spray, John G.; Bartoschewitz, Rainer (My University, 2005)
The Sayh al Uhaymir (SaU) 150 meteorite was found on a gravel plateau, 43.3 km south of Ghaba, Oman, on October 8, 2002. Oxygen isotope (δ17O 2.78; δ18O 4.74), CRE age (∼1.3 Ma), and noble gas studies confirm its Martian origin. SaU 150 is classified as an olivine-phyric basalt, having a porphyritic texture with olivine macrocrysts set in a finer-grained matrix of pigeonite and interstitial maskelynite, with minor augite, spinel, ilmenite, merrillite, pyrrhotite, pentlandite, and secondary (terrestrial) calcite and iron oxides. The bulk rock composition, in particular mg (68) [molar Mg/(Mg + Fe) × 100], Fe/Mn (37.9), and Na/Al (0.22), are characteristic of Martian meteorites. Based on mineral compositions, cooling rates determined from crystal morphology, and crystal size distribution, it is deduced that the parent magma formed in a steady-state growth regime (magma chamber) that cooled at <2 °C/hr. Subsequent eruption as a thick lava flow or hypabyssal intrusion entrained a small fraction of xenocrystic olivine and gave rise to a magmatic foliation, with slow cooling allowing for near homogenization of igneous minerals. SaU 150 experienced an equilibration shock pressure of 33–45 GPa in a single impact event. Post-shock heat gave rise to localized melting (∼11 vol%). Larger volume melts remained fluid after pressure release and crystallized dendritic olivine and pyroxene with fractal dimensions of 1.80–1.89 and 1.89–1.95, respectively, at −ΔT >70–365 °C. SaU 150 is essentially identical to SaU 005/094, all representing samples of the same fall that are similar to, but distinct from, the DaG shergottites.
Keywords: Martian meteorites; shock metamorphism; fractal analysis; crystal size distribution